Journalism, press freedom and Covid-19 - Sak, K.O.; Ryskeldinova, S.B.; Abdrakhmanova, A.; Toplu, M. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2021)
2019 has shocked the world with the disease COVID-19. The fight against the coronavirus, which was granted the status of «pandemic» by the decision of the World Health Organization continues. Kazakhstan has taken timely measures to protect its citizens in connection with the spread of the pandemic. The legitimacy, nature, and proportionality of these measures are reflected in this article. Kazakhstan declared a state of emergency on March 16, 2020, severely restricting the free movement of citizens and other basic freedoms as a response to the pandemic. Restrictions on quarantine made it difficult to disseminate information openly and unhindered. In particular, the work of journalists was obstructed. The author considers the problem of editorial independence as an important part of the professionalism of journalists in terms of foreign concepts. The author analyzes the contradictions between the normative approach to understanding the reality of the media market during the pandemic of freedom of speech.